A Longitudinal Cohort Study of Youth Mental Health and Substance use Before and During the COVID-19 Pandemic in Ontario, Canada: An Exploratory Analysis. (November 2022) - Sheikhan, Natasha Y.; Hawke, Lisa D.; Ma, Clement; Courtney, Darren; Szatmari, Peter; Cleverley, Kristin; Voineskos, Aristotle; Cheung, Amy; Henderson, Joanna
Background: Youth mental health appears to have been negatively impacted by the COVID-19 pandemic. The impact on substance use is less clear, as is the impact on subgroups of youth, including those with pre-existing mental health or substance use challenges. Objective: This hypothesis-generating study examines the longitudinal evolution of youth mental health and substance use from before the COVID-19 pandemic to over one year into the pandemic among youth with pre-existing mental health or substance use challenges. Method: A total of 168 youth aged 14–24 participated. Participants provided sociodemographic data, as well as internalizing disorder, externalizing disorder, and substance use data prior to the pandemic's onset, then every two months between April 2020–2021. Linear mixed models and Generalized Estimating Equations were used to analyze the effect of time on mental health and substance use. Exploratory analyses were conducted to examine interactions with sociodemographic and clinical characteristics. Results: There was no change in internalizing or externalizing disorder scores from prior to the pandemic to any point throughout the first year of the pandemic. Substance use scores during the pandemic declined compared to pre-pandemic scores. Exploratory analyses suggest that students appear to have experienced more mental health repercussions than non-students; other sociodemographic and clinical characteristics did not appear to be associated with mental health or substance use trajectories. Conclusions: While mental health remained stable and substance use declined from before the COVID-19 pandemic to during the pandemic among youth with pre-existing mental health challenges, some youth experienced greater challenges than others. Longitudinal monitoring among various population subgroups is crucial to identifying higher risk populations. This information is needed to provide empirical evidence to inform future research directions.